"Post Mastectomy Pain Syndrome: A Systematic Review of Prevention Modalities". (March 2022) - Yuksel, Selcen S.; Chappell, Ava G.; Jackson, Brandon T.; Wescott, Annie B.; Ellis, Marco F.
SUMMARY: Background: Post-mastectomy pain syndrome (PMPS) is a surgical complication of breast surgery characterized by chronic neuropathic pain. The development of PMPS is multifactorial and research on its prevention is limited. The objective of this systematic review is to synthesize the existing evidence on interventions for lowering the incidence of persistent neuropathic pain after breast surgery. Methods: Using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we performed a comprehensive search of the electronic databases of MEDLINE, Cochrane Library, Embase, CINAHL, PsycINFO, Web of Science, and ClinicalTrials.gov using a combination of database-specific controlled vocabulary and keyword searches. Two reviewers independently screened all unique records. Publications on chronic (>3-month duration) pain after breast cancer-related surgery were included. Studies were classified by modality. Results: Our literature search yielded 7092 articles after deduplication. We identified 45 studies that met final inclusion criteria for analysis, including 37 randomized-controlled trials. These studies revealed seven major intervention modalities for prevention of PMPS: physical therapy, mindfulness-based cognitive therapy, oral medications, surgical intervention, anesthesia, nerve blocks, and topical medication therapy. Conclusion: High-quality data on preventative techniques for PMPS are required to inform decisions for breast cancer survivors. We present a comprehensive assessment of the modalities available that can help guide breast and reconstructive surgeons employ effective strategies to lower the incidence and severity of PMPS. Our review supports the use of multimodal care involving both a peripherally targeted treatment and centrally acting medication to prevent the development of PMPS.